Organically bound tritium (OBT) activity concentrations in surface soil at the Chalk River Laboratories, Canada. (November 2019) - Kim, S.B.; Bredlaw, M.; Rousselle, H.; Farrow, F.; Carr, J.; Korolevych, V.Y.; Stuart, M.
Abstract: Canadian Nuclear Laboratories (CNL)'s Chalk River Laboratories (CRL) site is home to a large nuclear research complex in Canada. CRL's air tritium releases amount to about 10 15 Bq/year. The objective of the study was to characterize the spatial footprint of the 60 years of tritium atmospheric releases in surface soil by measurement of organically bound tritium (OBT). Soil OBT activity concentrations were of particular interest because soil represents a long-term tritium reservoir that can act as a historical record of tritium releases into the environment. Soil samples to a 5 cm depth were collected within the CRL site from 2012 to 2014. Each sample was analyzed for tritiated water (HTO) and OBT activity concentrations. The highest HTO and OBT measurements obtained during this study were 154.0 ± 7.8 Bq/L and 180.9 ± 37.3 Bq/L, respectively. A developed OBT map indicated that retained tritium in soil was not related to the distance of sources-term but it was related to the prevailing wind direction. Highlights: Characterize the spatial footprint of tritium atmospheric releases in the environment. Soil OBT activity concentrations were measured at the historical research reactor site. OBT contour map was produced to estimate the released tritium visually.